PROFITABILITAS SEBAGAI PEMODERASI PENGARUH UKURAN PERUSAHAAN TERHADAP PENGELUARAN ZAKAT PERUSAHAAN - Dewi Kusuma Wardani; Genduk Handini (AKURAT | Jurnal Ilmiah Akuntansi FE UNIBBA, 2021)
This study aims to analyze the effect of firm size on firm zakat with profitability as a moderating variable. The sample used is Islamic banking for the period 2015-2019, with a purposive sampling method and obtained 6 Islamic banks. This study used simple linear regression analysis and Moderated Regression Analysis (MRA). The results showed that firm size has no effect on firm zakat and profitability can’t moderate the effect of firm size on firm zakat